Dynamics of Fatwa DSN-MUI on Financing Products at Shari’ah Financial Institutions (LKS) from 2010 to 2021 - Ahmad Satiri; Beni Ahmad Saebani; Ah. Fathonih; Ending Solihuddin (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2025)
Sharia Economic Law develops in line with the development of Sharia Economics in Indonesia. This is certainly with the support of various stakeholders who handle it. It is interesting to discuss how DSN-MUI as an authority that issues fatwas related to sharia economics, especially in the field of financing, is able to balance the needs of Sharia Financial Institutions and customers until now the existence of Sharia Financial Institutions is getting better. This study is intended to examine the dynamics of sharia economic fatwas by DSN-MUI using analytical descriptive methods. It was found that DSN-MUI uses various methods and approaches in compiling fatwas that are in line with the needs of Sharia Financial Institutions while still adhering to the principles of Islamic law in the field of economics.